The etiology differs regards to the locations of the lesion: a clinical experience of 1350 patients with adenomyosis confirmed by postoperative pathology - Wanqing Li; Yuting Hang; Yunyu Xu; Wen Zhang; Ye He; Wei Ye; Xinyue Hu; Zhaolian Wei (BMC Women's Health)
Abstract Background Despite proposed mechanisms hypotheses, the etiology of adenomyosis remains unclear. The limited efficacy of current therapeutic approaches may stem from insufficient understanding of its pathobiological underpinnings and the pronounced heterogeneity in clinical presentation and treatment responsiveness among subtypes. This study seeks to compare clinical and sonographic profiles of adenomyosis subtypes to elucidate distinct disease mechanisms and inform subtype-specific management strategies. Methods In this retrospective cohort of 1,350 surgically treated and pathologically confirmed adenomyosis cases (2017–2022), patients were categorized into diffuse versus focal and anterior versus posterior lesion groups according to sonographic features. Comparative analyses of demographics, symptomatology, concurrent gynecological conditions, and laboratory profiles were conducted to delineate subtype-specific patterns. Results 1074 (79.56%) had a definitive adenomyotic sonographic signs, with 329 (30.63%) focal adenomyosis and 745 (69.37%) diffuse adenomyosis. Multivariate logistic regression analysis revealed that, compared with focal adenomyosis, diffuse adenomyosis were older (OR, 1.09; 95%CI: 1.06–1.12), had more pregnancies (OR, 1.22; 95%CI: 1.11–1.33), higher BMI (OR, 1.05; 95%CI: 1.00-1.09), long course of disease (OR, 1.06; 95%CI: 1.02–1.11) and higher risk of moderate to severe dysmenorrhea (OR, 1.88; 95%CI: 1.36–2.60). Divided to the location of adenomyosis lesion indicated by sonographic, patients in the posterior wall group (n = 418) have higher risk of moderate to severe dysmenorrhea (OR, 1.88; 95% CI: 1.36–2.60), more endometriosis combination (OR, 3.24; 95%CI: 1.85–5.68) and intraoperative blood loss (OR, 1.001; 95%CI: 1.001–1.003). Conclusion By stratifying adenomyosis into diffuse/focal and anterior/posterior subtypes, we identified distinct clinical-pathological profiles: (1) Diffuse adenomyosis was independently associated with older age, higher gravidity, and severe dysmenorrhea, suggesting a progressive phenotype driven by tissue injury mechanisms; (2) Posterior lesions exhibited a 3.24-fold risk of concurrent endometriosis and increased surgical complexity, implicating shared pathways with deep infiltrating endometriosis. These findings redefine adenomyosis as a heterogeneous disorder with subtype-specific pathophysiology, advocating for tailored therapeutic strategies.